Sustaining natural resources in African agriculture: What have we learned in the past two decades? - Place, Frank (Springer, 2022)
Calls for increased attention to natural resource management (NRM) in African agriculture have been around for many decades. They became more vocal around the turn of the century following decades of poor yield growth and emerging data showing concerns about land quality and productivity. In recent years, these intensified further with the specter of climate change and continuing rural population growth challenging agricultural systems on the continent. Researchers have responded to these challenges, advancing research frameworks and hypotheses, deploying more research tools, and conducting more studies. However, it is unclear that all this response has significantly advanced our state of knowledge on the extent and nature of land degradation in agricultural land, the particular practices that work in different socioeconomic contexts, and how best to induce their uptake by households facing different priorities and constraints. This chapter will motivate this conclusion and offer options for moving forward in some of these topical areas.